2023
DOI: 10.1007/s10555-023-10100-7
|View full text |Cite
|
Sign up to set email alerts
|

Considerations for modelling diffuse high-grade gliomas and developing clinically relevant therapies

Abstract: Diffuse high-grade gliomas contain some of the most dangerous human cancers that lack curative treatment options. The recent molecular stratification of gliomas by the World Health Organisation in 2021 is expected to improve outcomes for patients in neuro-oncology through the development of treatments targeted to specific tumour types. Despite this promise, research is hindered by the lack of preclinical modelling platforms capable of recapitulating the heterogeneity and cellular phenotypes of tumours residing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 264 publications
0
1
0
Order By: Relevance
“…Compared with primary cancer organoids, metastatic cancer organoids also exhibit a greater growth rate and volume both in vitro and in vivo [ 62 , 63 , 65 ]. However, healthy epithelial organoids unexpectedly exhibit greater proliferation than organoids cultured from primary cancer, creating an interesting contradiction [ 83 ]. Further studies are needed to understand and reconcile the contrasting growth rates observed between normal epithelial cells, metastatic cells, and primary cancer cells, which may help to address the question of whether normal epithelial cells can replace cancer cells in organoid cultures.…”
Section: Biobanks Of Organoids Derived From Metastatic Cancermentioning
confidence: 99%
“…Compared with primary cancer organoids, metastatic cancer organoids also exhibit a greater growth rate and volume both in vitro and in vivo [ 62 , 63 , 65 ]. However, healthy epithelial organoids unexpectedly exhibit greater proliferation than organoids cultured from primary cancer, creating an interesting contradiction [ 83 ]. Further studies are needed to understand and reconcile the contrasting growth rates observed between normal epithelial cells, metastatic cells, and primary cancer cells, which may help to address the question of whether normal epithelial cells can replace cancer cells in organoid cultures.…”
Section: Biobanks Of Organoids Derived From Metastatic Cancermentioning
confidence: 99%